Nurcholish Madjid and the Concept of Inclusive Islam in Indonesia: A Study of His Thoughts and Influence on Moderate Islam - Alam Khaerul Hidayat; Shofiyullah Muzammi (al-Afkar, Journal For Islamic Studies, 2025)
Nurcholish Madjid (Cak Nur) is one of the most influential Islamic thought reformers in Indonesia. His ideas on inclusive and moderate Islam have played an important role in encouraging the transformation of religious views in Indonesia, especially in facing the challenges of pluralism, democracy and modernity. This article examines Nurcholish Madjid's thoughts that focus on the concept of inclusive Islam, an Islam that respects diversity, is open to interfaith dialog, and is in harmony with the principles of democracy. Through a qualitative approach based on literature review, this article examines Nurcholish Madjid's thoughts on the concept of pluralism, religious moderation in Indonesia and the implications of these thoughts for interfaith relations, social stability, and strengthening democracy in Indonesia.